Project planning and project success : the 25% solution - Serrador, Pedro (Best practices and advances in program management series., 2015)
Project planning is generally accepted as an important contributor to project success. However, is there research that affirms the positive impact of project planning and gives guidance on how much effort should be spent on planning? To answer these questions, this book looks at current literature and new research of this under-studied area of project management. The author presents his findings from an extensive review of project planning literature that covers more than 270 sources. He also discusses new research that analyzes data from more than 1,300 global projects. The book confirms that the time spent on planning activities reduces risk and significantly increases the chances of project success. It also concludes that there can be too much planning and shows that the optimum ratio of planning to effort is 25%.